Impact of the Increased Recommended Dosage of Isoniazid on Pyridoxine Levels in Children and Adolescents. Issue 5 (May 2016) - Rodà, Diana; Rozas, Librada; Fortuny, Clàudia; Sierra, Cristina; Noguera-Julian, Antoni
Abstract : Isoniazid exposure causes dose-dependent pyridoxine deficiency. Recently, the recommended dosage of isoniazid in children was increased from 5 (4–6) to 10 (10–15) mg/kg/day. We aimed to analyze longitudinally pyridoxine levels in a cohort of previously healthy children and adolescents treated with isoniazid. Mild symptom-free pyridoxine deficiency was observed in 4/75 (5.6%) and 3/40 (7.5%) at baseline and at 3-month follow-up, respectively. Classical age-related risk factors identified patients at risk of pyridoxine deficiency. Our preliminary results support current recommendations regarding pyridoxine supplementation in healthy children. Abstract : Supplemental Digital Content is available in the text.